Investigating Socio-Cultural Factors affecting the Diagnosis of Children with Autism Spectrum Disorder (ASD) in South Punjab - Aftab, Muhammad Javed; Haider, Naeem; Amjad, Faisal (Annals of Human and Social Sciences, 2024)
This study investigates the socio-cultural factors influencing the diagnosis of Autism Spectrum Disorder (ASD) in South Punjab. The research analyzes data collected from 100 participants to understand perceptions regarding ASD awareness, access to healthcare services, cultural influences, Stigma associated with seeking a diagnosis, and healthcare providers’ cultural competence. Also parental awareness, socio-economic status impact, community-led awareness programs, the necessity of cultural competence training, and the role of government initiatives. Results indicate a lack of sufficient ASD awareness and access to healthcare services. 87% and 90% of respondents, respectively, expressed disagreement. However, opinions vary on the influence of cultural beliefs, stigma, and the necessity of cultural competence training for healthcare providers. T-tests and ANOVA were conducted to explore the association between demographic variables and perceptions of ASD diagnosis. The t-tests confirmed no statistically significant difference in means between genders (p = .509), and ANOVA revealed no significant differences in means across education levels (p = .304) or age groups (p = .436). This research contributes to understanding the complex socio-cultural dynamics impacting ASD diagnosis in South Punjab. This research contributes to implications for policy, healthcare practices, and community engagement initiatives.